Virushepatitis – wann daran denken? - Luxenburger, Hendrik; Thimme, Robert; Neumann-Haefelin, Christoph (DMW - Deutsche Medizinische Wochenschrift, 2019)
Chronic viral hepatitis can remain unrecognized but may nevertheless lead to liver cirrhosis and hepatocellular carcinoma. Thus, patients with elevated liver enzymes as well as risk groups need to be screened and treated for viral hepatitis. These groups include, in particular, migrants from countries with high HBV or HCV prevalence, persons with previous or current intravenous drug use, and homosexual men. For HBV- or HCV-associated diseases, such as panarteriitis nodosa, cryoglobulinemic vasculitis or B-cell lymphoma, antiviral therapy may lead to remission. Prior to high-dose immunosuppressive therapy, especially with regimes containing rituximab, chronic or resolved HBV infection must be ruled out or antiviral prophylaxis may be required to avoid a potentially fatal HBV reactivation.
Keywords: Hepatitis C; Hepatitis B; Hepatitis E; HBV-Reaktivierung; extrahepatische Manifestation